2016
DOI: 10.1371/journal.pgen.1005783
|View full text |Cite
|
Sign up to set email alerts
|

Glycine and Folate Ameliorate Models of Congenital Sideroblastic Anemia

Abstract: Sideroblastic anemias are acquired or inherited anemias that result in a decreased ability to synthesize hemoglobin in red blood cells and result in the presence of iron deposits in the mitochondria of red blood cell precursors. A common subtype of congenital sideroblastic anemia is due to autosomal recessive mutations in the SLC25A38 gene. The current treatment for SLC25A38 congenital sideroblastic anemia is chronic blood transfusion coupled with iron chelation. The function of SLC25A38 is not known. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 37 publications
(29 reference statements)
1
65
0
1
Order By: Relevance
“…Functional Characterization of Recombinant Hem25p-Because it has been hypothesized that Hem25p facilitates ALA production by importing glycine into mitochondria (13,14), the recombinant and purified Hem25p was reconstituted into liposomes, and its ability to transport glycine was tested. Proteoliposomes reconstituted with Hem25p catalyzed active […”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Functional Characterization of Recombinant Hem25p-Because it has been hypothesized that Hem25p facilitates ALA production by importing glycine into mitochondria (13,14), the recombinant and purified Hem25p was reconstituted into liposomes, and its ability to transport glycine was tested. Proteoliposomes reconstituted with Hem25p catalyzed active […”
Section: Resultsmentioning
confidence: 99%
“…In this subgroup of patients the author identified several mutations in the SLC25A38 gene (13). Furthermore, an anemic phenotype similar to that of ALAS2 deficiency has also been observed in the knockdown of two zebrafish orthologues of SLC25A38 (slc25a38a and slc25a38b), indicating that this gene is important for red blood cell production and function (13,14). It has been demonstrated that the genetic deletion of the Saccharomyces cerevisiae SLC25A38 ortholog YDL119c (also named HEM25) produces a respiratory pheno-type, indicative of mitochondrial involvement (13).…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…5-ALA é um dos principais precursores da via de síntese de HEME, o que poderia explicar o fenótipo apresentado pelos pacientes portadores da síndrome (FLEMING, 2011) FERNANDEZ-MURRAY et al, 2016).…”
Section: Resultados E Discussão Parcial -Ydl119cunclassified